The Effect of Antiretroviral Therapy Initiation on the Vaginal Microbiome in HIV-Infected Women. (12th July 2019) - Liu, Cindy M; Packman, Zoe R; Abraham, Alison G; Serwadda, David M; Nalugoda, Fred; Aziz, Maliha; Prodger, Jessica L; Kaul, Rupert; Kalibbala, Sarah; Gray, Ronald H; Price, Lance B; Quinn, Thomas C; et al.
Abstract: Background: The impact of antiretroviral therapy (ART) initiation on the vaginal microbiome is unknown. This is of particular importance among women living in sub-Saharan Africa. Understanding this relationship could help elucidate if and how the host immune system interacts with the vaginal microbiome. Methods: The vaginal microbiome of HIV-1/HSV-2-coinfected women (n = 92) in Uganda was evaluated from self-collected vaginal swabs 1 month pre-ART and at 4 and 6 months post–ART initiation. The vaginal microbiome was characterized by 16S rRNA gene-based sequencing and quantitative polymerase chain reaction. Vaginal community state types (CSTs) were identified using proportional abundance data. Changes in microbiome composition were assessed with permutational analyses of variance (PerMANOVA). Results: Five vaginal CSTs were identified, which varied significantly by bacterial load ( P < .01): CST-1 was characterized by Lactobacillus iners, CST-2 by Gardnerella, CST-3 by Gardnerella and Prevotella, CST-4 by Lactobacillus crispatus, and CST-5 was highly diverse. Vaginal microbiome composition also did not change significantly after ART initiation ( P = .985). Immune reconstitution after ART initiation did not affect vaginal microbiome CST assignment ( P = .722) or individual-level changes in bacterial load (log response ratio [interquartile range], –0.50 [–2.75 to 0.38] vs –0.29 [–2.03 to 1.42]; P = .40). Conclusions: The vaginal microbiome of HIV-infected women was not affected by the initiation of ART or immune reconstitution in this observational study. Further research is needed to explore the long-term effects of ART treatment on the vaginal microbiome.